2010
DOI: 10.1002/cctc.200900074
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed C3 or C4 Direct Arylation of Heteroaromatic Compounds with Aryl Halides by CH Bond Activation

Abstract: In recent years, palladium‐catalyzed direct C2 or C5 arylation of heteroaromatic compounds with aryl halides by CH bond activation has become a popular method for generating carbon–carbon bonds. For this reaction, a wide variety of heteroaromatics, such as furans, thiophenes, pyrroles, thiazoles, oxazoles, imidazoles, pyrazoles, indoles, triazoles, or even pyridines, can be employed. C3 and C4 arylations of heteroaromatics by CH bond activation have also been described. Such reactions initially attracted muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(103 citation statements)
references
References 122 publications
1
94
0
8
Order By: Relevance
“…5 However, most of the reactions were known to occur preferentially at the α-position of thiophene rings when both α-and β-positions are available, and a general method for the selective functionalization of the β-position had not been reported. 6 In 2009, our group established a general protocol for the programmed synthesis of tetraarylthiophenes 4 through sequential CH couplings (Scheme 1). 7 During this experiment, the β- selectivity observed in the arylation of methoxy-substituted thiophenes 1 with iodoarenes 2 under the catalysis of PdCl 2 / P[OCH(CF 3 ) 2 ] 3 /Ag 2 CO 3 was an intriguing phenomenon.…”
Section: Regioselective Ch Arylation Of Thiophenes Thiazoles and Pymentioning
confidence: 99%
“…5 However, most of the reactions were known to occur preferentially at the α-position of thiophene rings when both α-and β-positions are available, and a general method for the selective functionalization of the β-position had not been reported. 6 In 2009, our group established a general protocol for the programmed synthesis of tetraarylthiophenes 4 through sequential CH couplings (Scheme 1). 7 During this experiment, the β- selectivity observed in the arylation of methoxy-substituted thiophenes 1 with iodoarenes 2 under the catalysis of PdCl 2 / P[OCH(CF 3 ) 2 ] 3 /Ag 2 CO 3 was an intriguing phenomenon.…”
Section: Regioselective Ch Arylation Of Thiophenes Thiazoles and Pymentioning
confidence: 99%
“…On the other hand, carbons C-2 and C-5 of the pyrrole ring are known to be more reactive than C-3 and C-4 in the Pd-catalyzed direct arylations. [24] In 1995, Gryko and co-workers reported that Nalkyl-2-arylpyrroles and 1,2-diarylpyrroles could be obtained in modest to good yields by treatment of 1 equiv. of (hetero)aryl iodides with 5 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Pyrrole mentioning
confidence: 99%
“…In particular, the deve lopment of a catalyst promoting the hard to achieve arylation at the β position of the thiophene ring was crucial. 32 Extensive screening led to the development of two new Pd catalysts (Cat A and Cat B) for the second and third arylations of 3, respectively (Scheme 17). 30 We fi rst found that the otherwise diffi cult C4 selective arylation of 4a with iodoarenes can be promoted by the catalyst PdCl 2 With two regiodivergent C H arylation catalysts in hand, the third C H arylation for making 2,4,5 triaryl 3 methoxythiophenes 6 was next examined for two possible routes, one via 8, the other via 5 (Scheme 18).…”
Section: Programmed Synthesis Of Tetraarylthiophenes: Regioselec Tivementioning
confidence: 99%